Intentional social distance regulation alters affective responses towards victims of violence: An FMRI study - Leiberg, S; Eippert, F; Veit, R; Anders, S (2012)
We used functional magnetic resonance imaging (fMRI) to investigate brain processes underlying control of emotional responses towards a person in distress by cognitive social distance modulation. fMRI and peripheral physiological responses (startle response and electrodermal activity) were recorded from 24 women while they watched victim-offender scenes and modulated their social distance to the victim by cognitive reappraisal. We found that emotional responses, including startle eyeblink and amygdala responses, can effectively be modulated by social distance modulation. Furthermore, our data provide evidence that activity in the dorsomedial prefrontal cortex (dmPFC) and the anterior paracingulate cortex (aPCC), two brain regions that have previously been associated with brain processes related to distant and close others, is differentially modulated by intentional social distance modulation: activity in the dmPFC increased with increasing disengagement from the victim and activity in the aPCC increased with increasing engagement with the victim. We suggest that these two regions play opposing roles in cognitive modulation of social distance and affective responses towards persons in distress that enable the adaptive and flexible social behavior observed in humans. © 2011 Wiley Periodicals, Inc.